DETECTION OF HELICOBACTER PYLORI INFECTION IN CHRONIC GASTRITIS BIOPSY SPECIMEN USING WARTHIN-STARRY AND MODIFIED GIEMSA STAIN IN DR SOETOMO HOSPITAL SURABAYA - Sandhika, Willy (Indonesian Journal of Tropical and Infectious Disease, 2019)
Helicobacter pylori is a bacteria that commonly cause chronic gastritis. Identification of its infection is essential for eradication treatment. Detection of H.pylori bacteria in gastric biopsy specimen by histology method is a diagnostic tool that widely accepted because it is superior to serology examination. Although the bacteria can be seen in routinely Hematoxylin-Eosin staining, Modified Giemsa and Whartin Starry stain was commonly used to see the bacteria more clearly. Whartin Starry stain gives more contrast to the bacteria but modified Giemsa stain is preferable at many centres because it is a cheaper and simpler method. This study want to find out whether there is difference result in detection of H.pylori using these two stains. Material and methods. Paraffin blocks from gastric biopsy patients with chronic gastritis were retrieved from Anatomic Pathology Laboratory Dr.Soetomo Hospital Surabaya in the year 2017. Thirty paraffin blocks were taken randomly and were made into microscopic slides for staining with Warthin-starry and modified Giemsa stain concomitantly. Results. Specimen with Whartin starry stain show 19 out of 30 were positive for H.pylori while modified-Giemsa stain found 16 out of 30 specimen were positive for H.pylori. Whartin Starry stain use silver reagent to coat the bacteria so it become more clearly visible. Conclusion. Detection of H.pylori Warthin-starry stain give more chance to obtain positive result because it use silver technique that coat the bacteria making it is more clearly visible in microscopic examination.